La planificación familiar en China: la política de un solo hijo por familia - Pan, Lien-Tan (El Colegio de México, 2014)
In 1979, given the extraordinary population growth rate and the lack of resources to feed its population, China decided to establish the one-child policy. However, although the said policy managed to control population growth after a while, it brought along another set of problems such as gender disparity, the lost girls, an aging population, and the ‘little emperors’. This article provides a brief history of family planning in China to then explore the one-child policy, its implementation, practice, and criticisms, as well as its future.